The Intensive Care Nurses’ Knowledge and Practice of Endotracheal Suctioning Intubated Patients in Tertiary Care Public Sector Hospitals in Karachi, Pakistan : Intensive Care Nurses’ Knowledge and Practice of Endotracheal Suctioning - Fauzia Rafiq; Badil; Hussain , Mehwish; Saeed, Muhammad Farooq Saeed; –, Gohar Ur Rehman (Pakistan Journal of Health Sciences, 2022)
Endotracheal suctioning is a prime and most common invasive procedure accomplished by inserting an artificial tube in the patient’s airway. Objectives: To evaluate nurses’ knowledge and practice regarding intubated patients’ endotracheal suctioning in the intensive care units in the tertiary care hospital of Karachi, Pakistan. Methods: The descriptive cross-sectional study design was accomplished on intensive care unit nurses from two tertiary care public sector hospitals. A validated and adopted questionnaire was used to collect data. Data were entered and analyzed by using SPSS version 21. A p-value ≤ 0.05 was considered as significant. Results: Out of a total of 80 nurses, 57.5% of the participants were males. Male participants’ mean knowledge level of ES was 9.0 with SD 2.1 and females with 9.9 with SD 2.3. The mean knowledge level of the female participants was higher than male. Insignificant differences were found among the mean knowledge levels of the male and female participants, with a p-value of p=0.075. Furthermore, the mean score (11.4 ± 1.1 SD) of the practice level of male participants was higher than the mean score (10.8 ± 1.3 SD) of female participants. An insignificant difference was found between the mean practice level of males and females, with a p-value of p=0.126. Conclusions: It was concluded that the study’s participants working in ICUs of tertiary care hospitals have good knowledge and practice of endotracheal suctioning